Penguatan Kecerdasan Interpersonal Siswa melalui Integrasi STAD dan NHT dalam Cooperative Learning pada Pembelajaran Fikih - Sofiah, Rifatun; ⁠Fina Surya Anggraini; ⁠Hasyim Asy'ari (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to analyze the implementation of multi-technique cooperative learning through Student Teams Achievement Division (STAD) and Numbered Heads Together (NHT), and to examine its implications for developing students’ interpersonal intelligence in Islamic education learning, specifically in fiqh classes at MAN 1 Mojokerto. The study addresses the need for more dynamic and interactive learning strategies that not only improve cognitive achievement but also enhance students’ social competencies in the 21st-century learning context. Design/methods – This study employed a qualitative approach with an intrinsic case study design. The research data were collected through six classroom observations, in-depth interviews with one Islamic education (Fiqh) teacher and ten students, as well as documentation of learning activities in classes XI KMP 6 and XI KMP 8, with a total of 32 students as the research context. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. Data validity was ensured through source triangulation (teachers, students, and the vice principal of curriculum) and technique triangulation (observation, interviews, and documentation) to enhance the credibility of the research findings. Findings – The findings reveal that the integration of STAD and NHT created a more active, interactive, and participatory learning environment. STAD enhanced group collaboration through positive interdependence among students, while NHT strengthened individual accountability in mastering learning materials. The combination of both techniques contributed to the development of students’ interpersonal intelligence, reflected in improved social skills, communication abilities, leadership behavior, and empathy. The classroom interaction patterns indicate that cooperative learning provides an effective space for fostering both academic engagement and social character development.